Candida auris Fungemia and a local spread taken under control with infection control measures: First report from Turkey - Kurt, Ahmet Furkan; Kuşkucu, Mert; Balkan, İlker İnanç; Bayri Barış, Ayşe; Yazgan, Zeynep; Öz, Ayşe Şerife; İstanbullu Tosun, Ayşe; Mete, Bilgül; Tabak, Fehmi; Aygün, Gökhan (NLM (Medline), 2021)
Candidaauris, draws attention as a new emerging antifungal resistant pathogen, leading to healthcare-associated infections and outbreaks. This is the first report of C. auris fungemia in a 81-year-old patient, confirmed by sequential analysis, from Turkey. Although the source of the isolate could not be identified, its spread in the hospital has been taken under control by effective infection control measures.
Keywords: Candida Auris; Local Spread; Turkey